Corporate Security of Forest Employees - Chaturvedi, M. D. (Indian Forester, 1943)
The creation of a Forest Subordinates' Corporate Security Fund will, apart from simplifying security accounts which involve an appalling waste of time in forest offices, instil a spirit of co-operation and esprit de corps among forest employees. The proposed scheme in its briefest outline envisages the replacement of individual by corporate security.